Forty years of ocean acidification observations (1983–2023) in the Sargasso Sea at the Bermuda Atlantic Time-series Study site - Bates, Nicholas R.; Johnson, Rodney J. (Frontiers in Marine Science, 2023)
The scope of this original research article focused on the ocean physics, biogeochemistry and ocean acidification status of the subtropical North Atlantic Ocean at the Bermuda Atlantic Time-series Study (BATS) site near Bermuda. This paper provides the longest sustained time-series in the global ocean on ocean acidification with data and trends over the past forty years (1983 to 2023). This paper provides a perfect introduction and fit to this special issue of ocean acidification. Importantly, over this period, the ocean has warmed by about +1°C, increased in salinity by +0.136, and lost dissolved oxygen (DO) by 12.5 µmol kg -1 or ~6%. Along with increases in ocean dissolved inorganic carbon (DIC), total alkalinity (TA), anthropogenic CO2 (i.e., CANT) and fugacities/partial pressures of CO2 (i.e., fCO2 and pCO2),ocean pH has decreased by ~0.1 pH units (with ocean acidity (i.e., H + ) increasing by >30%) and saturation states of calcium carbonate minerals (Wcalcite and Waragonite) have decreased. These ocean acidification (OA) indicators show the chemical conditions for calcification becoming less favourable, how ocean chemistry of the 2020s is now outside the range observed in the 1980s, and essential data for predicting how ocean chemistry and marine ecosystems will respond to future shifting earth and ocean conditions.